Enhancement the production of lipase derived from Bukhoderia cenopacia ST8 by optimization of the fermentation operation - Show, Pau Loke; Anuar, Mohd Shamsul; Yusof, Yus Aniza; Ariff, Arbakariya; Ling, Tau Chuan (Faculty of Engineering, Universiti Putra Malaysia, 2012)
A lipase derived from Burkhoderia cenocepacia ST8 was optimized in this research. The experimental design based on ‘change-one-factor-at-a-time’ approach was applied to optimize the production of lipase. Parameters such as volume ratio of medium volume to container volume, concentration of carbon source, nutrient broth and metal ions of medium on lipase production were extensively studied. The optimum conditions in cultivation medium containing 1% (w/v) Tween 80, 0.3% (w/v) of nutrient broth and 0.1% (w/v) of CaCl2 with volume ratio 20:80 of medium volume to container volume, a high average production of 43.8 U/mL was obtained. Therefore, the optimum formulations and conditions would produce high yield of lipase were potential utilized in the commercial industrial.